Fearless Woman: Financial Literacy and Stock Market Participation - Tabea Bucher-Koenen; Rob Alessie; Annamaria Lusardi; Maarten van Rooij (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Women are less financially literate than men. It is unclear whether this gap reflects a lack of knowledge or, rather, a lack of confidence. Our survey experiment shows that women tend to disproportionately respond 'do not know' to questions measuring financial knowledge, but when this response option is unavailable, they often choose the correct answer. We estimate a latent class model and predict the probability that respondents truly know the correct answers. We find that about one-third of the financial literacy gender gap can be explained by women's lower confidence levels. Both financial knowledge and confidence explain stock market participation.
Keywords: G53; C81; D91; 330; financial knowledge; gender gap; financial decision making; confidence; measurement error; latent class model; finite mixture model